Baks Oil Sdn Bhd / Mohd Syahrizal Mohd Bakri... [et al.] - Shaari, Abdul Kadir; Abdullah, Azmi; Selamat, Badrul Iskandar; Mohd Bakri, Mohd Syahrizal (2001)
Baks Oil Sdn Bhd is a private company that involved in palm oil business. Their factory stated in Alor Setar Kedah.Their main business are processing and packaging cooking oil. Their business started on 1 January 2003